Analisis Implemetasi Program Lingkungan Hidup oleh Lazismu Atas Dasar Ijtihad Majelis Tarjih Muhammadiyah - Bagus Ardeni; Amrizal; Iwan Setiadi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the strategies and mechanisms that LazisMu can adopt to ensure alignment between its environmental objectives and operational activities. The primary focus is on the application of ijtihad and tajdid of Muhammadiyah in environmental issues, guided by Islamic economic principles. Employing a qualitative approach with a descriptive-analytical method, this study examines the Islamic economic framework within environmental contexts and the implementation of LazisMu’s environmental initiatives. Additionally, in-depth interviews were conducted to gather primary data. Findings indicate two key insights. First, LazisMu has embraced environmental ijtihad as directed by Majelis Tarjih Muhammadiyah, transitioning from a traditional philanthropic institution into a catalyst for social and environmental transformation. Since 2020, this concept has been realized through the publication of Fikih Air and programs such as “Sayangi Daratmu,” “Program Tanam Pohon,” and “Sayangi Lautmu,” emphasizing ecosystem rehabilitation and community-based waste management. Furthermore, LazisMu optimizes Islamic financial instruments by leveraging zakat, infaq, and sadaqah in progressive funding schemes, such as tree adoption models and biogas utilization as sustainable energy. To ensure long-term impact, these initiatives are monitored through IKU and IKAL, while digital education reinforces zakat’s role as a driver of socio-environmental transformation.